Silver Nanoparticles Combined With Naphthoquinones as an Effective Synergistic Strategy Against Staphylococcus aureus - Krychowiak, Marta; Kawiak, Anna; Narajczyk, Magdalena; Borowik, Agnieszka; Królicka, Aleksandra (Frontiers in Pharmacology, 2018)
Staphylococcus aureus is a human pathogen responsible for many antibiotic-resistant infections, for instance burn wound infections, which pose a threat to human life. Exploring possible synergy between various antimicrobial agents, like nanoparticles and plant natural products, may provide new weapons to combat antibiotic resistant pathogens. The objective of this study was to examine the potential of silver nanoparticles (AgNPs) to enhance the antimicrobial activity of selected naphthoquinones (NQs): plumbagin (PL), ramentaceone (RAM), droserone (DR), and 3-chloroplumbagin (3ChPL). We also attempted to elucidate the mechanism by which the AgNPs enhance the antimicrobial activity of NQs. We analyzed the interaction of AgNPs with bacterial membrane and its effect on membrane stability (TEM analysis, staining with SYTO 9 and propidium iodide), as well as aggregation of NQs on the surface of nanoparticles (UV-Vis spectroscopy and DLS analysis). Our results demonstrated clearly a synergistic activity of AgNPs and three out of four tested NQs (FBC indexes ≤0.375). This resulted in an increase in their combined bactericidal effect towards the S. aureus reference strain and the clinical isolates, which varied in resistance profiles. The synergistic effect (FBC index = 0.375) resulting from combining 3ChPL with silver nitrate used as a control, emphasized the role of the ionic form of silver released from nanoparticles in their bactericidal activity in combination with NQs. The role of membrane damage and AgNPs-NQ interactions in the observed synergy of silver nanoparticles and NQs was also confirmed. Moreover, the described approach, based on the synergistic interaction between the above mentioned agents enables a reduction of their effective doses, thus significantly reducing cytotoxic effect of NQs towards eukaryotic HaCaT cells. Therefore, the present study on the use of a combination of agents (AgNPs-NQs) suggests its potential use as a possible strategy to combat antibiotic-resistant S. aureus.